Telling It Like It Is - Darensbourg, Joe. author. aut Link
VIII, 264 p.
Keywords: The autobiography of one of the foremost jazz clarinetists who is well known for his recordings with Edward 'Kid' Ory and the Louis Armstrong All Stars. Darensbourg was born in Baton Rouge, LA, in 1906 and heard many early New Orleans jazz bands as a young boy. For most of his life he lived on the West Coast and the book is a first-rate reference source for students of jazz and popular music in the urban centres of Seattle and Los Angeles.